Prevalence, pattern, and predictors of formal help-seeking for intimate partner violence against women: findings from India's cross-sectional National Family Health Surveys-3 (2005-2006) and 4 (2015-2016) - Suman Kanougiya; Muthusamy Sivakami; Nayreen Daruwalla; David Osrin (BMC, 2022)
Abstract Background Help-seeking for intimate partner violence (IPV) requires women to disclose their experiences. For policymakers, low help-seeking threatens the United Nations Sustainable Development Goals (SDGs) of gender equality, good health, and wellbeing. In India, the Prevention of Domestic Violence Against Women Act (PWDVA 2005) was implemented in 2006. Using two rounds of the India National Family Health Survey (NFHS), one before and one after implementation, we examined the prevalence, pattern, and sociodemographic and socioeconomic factors associated with formal help-seeking for IPV. Methods We used univariable and multivariable logistic regression models to assess the prevalence of help-seeking for IPV in the past 12 months and examined associations with different forms of IPV and sociodemographic factors. Results The proportion of ever-married women aged 15-49 years who reported physical, sexual, or emotional IPV in the last 12 months increased from 23% in NFHS-3 (2005-2006) to 25% in NFHS-4 (2015-2016). In both surveys, few women sought help. Informal sources of help were preferred over formal sources, which declined from NFHS-3 to NFHS-4 (any help: 24.5 to 13.8%; informal help: 24.1 to 13.4%; and formal help: 1.2 to 1.1%). Women from lower castes and women with children were less likely to seek formal help. Over the two surveys, the odds of formal help-seeking for sexual IPV in the past 12 months remained similar (NFHS-3 aOR 1.9, 95% CI 1.4, 2.5. NFHS-4 aOR 1.9, 95% CI 1.4, 2.6). The odds were slightly higher for emotional IPV (NFHS-3 aOR 2.5, 95% CI 1.8, 3.3. NFHS-4 aOR 2.7, 95% CI 2.0, 3.7) and spousal control (NFHS-3 aOR 2.0, 95% CI 1.4, 3.0. NFHS-4 aOR 2.3, 95% CI: 1.4, 3.7). Conclusions Low disclosure and help-seeking impact a country's social, cultural, economic, and political progress. The PWDVA did not appear to result in increases in help-seeking among women in India who experienced IPV. Further work is needed to understand barriers to help-seeking in the presence of public policy efforts to support women affected by IPV. These may include poor implementation and enforcement of Policy, as well as normalization and justification of gender-based violence. We recommend a deeper understanding of help-seeking across all systems to establish a barometer of help-seeking. An increase in formal or informal help-seeking is an indicator of reduced tolerance of IPV and the enabling environment of the PWDVA 2005 for tracking progress toward the SDGs of gender equality and the eradication of all forms of gender-based violence and discrimination.